Penyembunyian Pesan Pada File Audio Menerapkan Metode Chineseremainder Theorem - Josferi Pardosi (STMIK Budi Darma, 2021)
Information which is the result of processing from data has a different value for each person. Often information becomes very valuable and not everyone is allowed to know it, but there are always parties who try to find out information in ways that are not supposed to even intend to destroy it. There are several methods in steganography, one of which is a method to hide secret messages (text or images) in other files containing text, images, and even audio without showing any real or visible changes in the quality and structure of the original file. . These methods include invisible ink, microdots, word management, digital signatures, hidden paths and wide spectrum communications. Chineses Reminder Theorem (CRT) is a concept based on congruent relationships. However, in contrast to congruence in general, this concept is based on a simultaneous congruence relationship. Simultaneous congruence refers to several congruent relationships that have a relationship with one another, and this relationship is related to the same variable value but with different modules. This theory is an ancient theory that is often used in cryptographic applications.